Pengaruh Sosial Media Marketing dan Online Review terhadap Pembelian Berulang di Kopi Kenangan Kota Medan: Penelitian - Onan Marakali Siregar; Yossie Rossanty; Chika Naibaho; Ariq Wiratama Nasution; Dear Selvanathan Sinaga (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the partial and simultaneous influence of social media marketing and online reviews on repurchase intention among Kopi Kenangan customers in Medan City. This research employs a quantitative approach, with data collected through questionnaires distributed using a purposive sampling technique to 106 respondents who met the specified criteria. The collected data were analyzed using multiple linear regression analysis with the aid of SPSS software. The results indicate that social media marketing has a significant positive partial effect on repurchase intention (tstatistic​ = 7.256 > ttable​ = 1.659). Similarly, online reviews also show a significant positive partial effect on repurchase intention (tstatistic​ = 4.560 > ttable​ = 1.659). Simultaneously, both independent variables have a significant effect on repurchase intention (Fstatistic​ = 26.408 > Ftable​ = 3.09). The coefficient of determination (R2) of 0.339 indicates that 33.9% of the variance in repurchase intention can be explained by social media marketing and online reviews, while the remainder is influenced by other factors. These findings confirm that digital engagement through social media and the management of online reputation are crucial strategies for fostering loyalty and repeat purchases in the modern coffee shop industry.